Terminological lexicon in modern explanatory lexicography: the problem of selecting and marking - Томіленко, Людмила Миколаївна (Philological Studies: the Scientific Publication of Kryvyi Rih State Pedagogical University, 2014)
The article discusses the role of terminology are in explanatory dictionaries. We study the criteria for the introduction of terms in common language dictionaries, the problem marking. Propose some recommendations for the submission and marking of special vocabulary.